Transcriptomic Response of Mussel Gills After a Vibrio splendidus Infection Demonstrates Their Role in the Immune Response - Saco, Amaro; Rey-Campos, Magalí; Novoa, Beatriz; Figueras, Antonio (Frontiers in Immunology, 2020)
Mussels (Mytilus galloprovincialis) are filter feeder bivalves that are constantly in contact with a wide range of microorganisms, some of which are potentially pathogenic. How mussels recognize and respond to pathogens has not been fully elucidated to date; therefore, we investigated the immune mechanisms that these animals employ in response to a bacterial bath infection from the surrounding water, mimicking the response that mussels mount under natural conditions. After the bath infection, mussels were able to remove the bacteria from their bodies and from the water tank. Accordingly, antibacterial activity was detected in gill extracts, demonstrating that this tissue plays a central role in removing and clearing potential pathogens. A transcriptomic study performed after a bath infection with Vibrio splendidus identified a total of 1,156 differentially expressed genes. The expression levels of genes contributing to a number of biological processes, such as immune response activation pathways and their regulation with cytokines, cell recognition, adhesion and apoptosis, were significantly modulated after infection, suggesting that the gills play important roles in pathogen recognition, as well as being activators and regulators of the mussel innate immune response. In addition to RNA-seq analysis, long non-coding RNAs and their neighbouring genes were also analysed and exhibited modulation after the bacterial challenge. The response of gills against bath infection was compared with the findings of a previous transcriptomic study on hemocytes responding to systemic infection, demonstrating the different and specific functions of gills. The results of this study indicate that recognition processes occur in the gill, thereby activating the effector agents of the immune response to overcome bacterial infection.